The cisternal segment of the abducens nerve in man: three-dimensional MR imaging - Alkan, A; Sigirci, A; Ozveren, AF; Kutlu, R; Altinok, T; Onal, C; Sarac, K (Elsevier Sci Ireland Ltd, 2004)
Purpose: The goal of this study was to identify the abducens nerve in its cisternal segment by using three-dimensional turbo spin echo T2-weighted image (3DT2-TSE). The abducens nerve may arise from the medullopontine sulcus by one singular or two separated rootlets. Material and methods: We studied 285 patients (150 males, 135 females, age range: 9-72 years, mean age: 33.3 +/- 14.4) referred to MR imaging of the inner ear, internal auditory canal and brainstem. All 3D T2-TSE studies were performed with a 1.5 T MR system. Imaging parameters used for 3DT2-TSE sequence were TR:4000, TE:150, and 0.70 mm slice thickness. A field of view of 160 mm and 256 x 256 matrix were used. The double rootlets of the abducens nerve and contralateral abducens nerves and their relationships with anatomical structures were searched in the subarachnoid space. Results: We identified 540 of 570 abducens nerves (94.7%) in its complete cisternal course with certainty. Seventy-two cases (25.2%) in the present study had double rootlets of the abducens nerve. In 59 of these cases (34 on the right side and 25 on the left) presented with unilateral double rootlets of the abducens. Thirteen cases presented with bilateral double rootlets of the abducens (4.5%). Conclusion: An abducens nerve arising by two separate rootlets is not a rare variation. The detection of this anatomical variation by preoperative MR imaging is important to avoid partial damage of the nerve during surgical procedures. The 3DT2-TSE as a noninvasive technique makes it possible to obtain extremely high-quality images of microstructures as cranial nerves and surrounding vessels in the cerebellopontine cistern. Therefore, preoperative MR imaging should be performed to detect anatomical variations of abducens nerve and to reduce the chance of operative injuries. (C) 2003 Elsevier Ireland Ltd. All rights reserved.
Keywords: abducens nerve; double rootlets; magnetic resonance imaging